Quest for State Police in Nigeria - Nu’uman, Mohammed Habib (ESUT JOURNAL OF SOCIAL SCIENCES, 2025)
Since the return to civil rule in 1999, after a long interregnum of military rule, the call for the devolution of powers to the lower levels has become more strident. While the more extremist agitators have called into question the very existence of the Nigerian federation, demanding that it be dismantled, others have been more tempered, urging that a confederal arrangement should be put in place, whittling down the powers of the government at the centre. However, even among those not disposed to either of these two positions, there appears to be some support for the view that the Nigeria Police require some radical reform, including the creation of State Police to be fully under the charge of state governors. This paper explores the debate for the creation of state police, arguing that the call is but symptomatic of the poverty of leadership in the Nigerian state